The Impact Of Government Spending On Gross Domestic Product Of The Private Sector In Jordan (1990-2018) - Adham Taher Mohmmad Alessa; Hartini Mohammad (Malaysian Financial Planning Council, 2024)
This study aimed to investigate the impact of government spending on the real total local output of the private sector in Jordan by focusing on time series analysis of selected variables during the period 1990 to 2018. The objective was achieved using the appropriate statistical tests such as data stability and co-integration tests. The variables analysed included the real governmental spending (RGP), the real total output of the Private Sector (RPSP), Remittances of Workers (RRE), Energy Prices (RPP) and Inflation Rate (RINR). This study found a long-term statistically significant correlation between government spending and GDP of the private sector. It also found that long-term complementary relationships exist between the real total local output of the private sector and the variables used in the study. The study recommends the Jordanian government implement a targeted fiscal policy to support the economic activities in the Kingdom, provide customs and tax exemptions and provide appropriate infrastructure to encourage the private sector to invest. This is in addition to providing an appropriate environment for investment and removing the obstacles to investment in general in order to attract the capital of Jordanians working abroad for domestic investment, and foreign investments.